Allelopathy Effect of the Blue Diatom HasleaOstrearia (Gaillon) Simonsen: Growth Inhibition in Aquaculture Relevant Microalgae - Eko Windarto; Fiddy Semba Prasetiya; Jean-Luc Mouget; Romain Gastineau (International Journal of Marine and Aquatic Resource Conservation and Co-existence, 2014)
We are well known that the marine pennate diatom Hasleaostrearia (Gaillon) Simonsen produces the blue-green pigment called marennine. Marennine was identified as a polyphenolic compound. This compound is capable to inhibit the growth of herpes simplex virus type 1 (HSV-1) and several bacteria, including pathogens as Vibrio sp. The aim of this study was to determine how strong the allelophatic effect of marennine is generated byH. ostrearia and identifying its minimal concentration that inhibits the growth of other microalgae. The experiment consisted of two phases of research activities. The first phase was biovolumecomparaison between H. ostrearia and microalgae suitable for aquaculture tested to take into account the differences in size of the microalgae tested(Tetraselmissuecica, Chaetocerosgracilis, Skeletonemacostatum, PavlovalutheriandIsochrysisgalbana (T-Iso) in term of H. ostrearia biomass and production of marennine. The second phase was the bioactivity tests, which is include growth kinetics, allelophatic effects and concentration of marennine in the culture medium, measured with spectrophotometer. The results of this study showed that H. ostrearia could inhibit several species of microalgae currently used in aquaculture (T. suecica, C. gracilis and S. costatum). The statistical analysis (One way ANOVA) showed that there are significant differences (P < 0, 05) between treatments andwhen co-cultured with H. ostrearia, these microalgae exhibited a significant growth inhibition. The highest inhibition value was 97.77% (on the treatementH. ostrearia+C. gracilis). In this treatment, the concentration of marennine in the culture was 5.35 mg L-1. According to the results, we can conclude that the supernatant of H. ostrearia with marennine acts as an allelochemical. The minimal concentration is 0.23 mg L-1 and the highest is 5.35 mg L-1. The treatments H. ostreariawithP. lutheri and T-Iso did not performed any inhibition.   Key words: H. ostrearia, marennine, microalgae and Allelopathic effect.